Perlindungan Hak Waris Anak Luar Kawin Pasca Putusan MK Nomor 46/PUU-VIII/201 : Studi Analisis Putusan Nomor 239/Pdt.G/2015/PN.Jkt.Pst - Rayi Kharisma Rajib; Davina Fitri Rahmania; Nabila Aufa Shofiana (CV. ITTC INDONESIA, 2026)
Protection of the inheritance rights of illegitimate children is a crucial issue in the development of family law in Indonesia, particularly following the Constitutional Court's decision that strengthened the recognition of children's civil relationship with their biological fathers. This article aims to analyze the legal protection of illegitimate children's inheritance rights following the Constitutional Court's decision and to examine the judges' considerations in Decision Number 239/Pdt.G/2015/PN Jkt.Pst. This research uses a normative juridical method with a regulatory and case-based approach. The results show that the Constitutional Court's decision has provided a stronger legal basis for illegitimate children to obtain inheritance rights, generally demonstrating a blood relationship with their biological father. However, in judicial practice, differences in judges' interpretations regarding the status and distribution of illegitimate children's inheritance rights remain. In Decision Numbe r239/Pdt.G/2015/PN Jkt.Pst., judges consider aspects of justice, legal certainty, and evidence of biological relationships in determining inheritance rights, although this does not yet fully reflect uniform application of the norm. Therefore, consistency in law enforcement and strengthening of regulations are needed to ensure optimal protection of the rights of illegitimate children.